Analisis Perbandingan ROA Dan DER PT. Indofood Sukses Makmur Tbk Dengan PT. Mayora Indah Tbk - Alyah Nafisyah; Alwi Alwi (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This study aims (1) to determine whether there is a significant difference in Return On Assets (ROA) at PT. Indofood Sukses Makmur Tbk with PT. Mayora Indah Tbk, (2) To determine whether there is a significant difference in the Dept. To Equity (DER) at PT. Indofood Sukses Makmur Tbk with PT. Mayora Indah Tbk. This type of research uses a comparative method. The population used is the company's financial statements PT Indofood Sukses Makmur Tbk for 28 years and PT Mayora Indah Tbk for 32 years. The sample in this study was 7 years old using a sampling technique, namely purposive sampling. The analysis technique uses the Independent Sample T-test. Based on the results of data analysis using the Independent Sample T-test, it shows that there is a significant difference in Return On Assets (ROA) of PT. Indofood Sukses Makmur Tbk with PT. Mayora Indah Tbk and there is no significant difference in Debt To Equity (DER) PT. Indofood Sukses Makmur Tbk with PT. Mayora Indah Tbk.